Remote Targets for Right Coronary Artery Bypass: Distal Trunk or Posterior Descending Artery Grafting - Songur, Murat C.; Vural, Kerem M.; Erdolu, Burak; Ozyalcin, Sertan (The Thoracic and Cardiovascular Surgeon, 2015)
Background Choosing a good anastomotic site is crucial during surgical revascularization of the right coronary artery (RCA) system. In many instances of distal and/or sequential main trunk disease, either the right posterior descending coronary artery (RPDA) or distal part of the right main coronary artery (DRCA) is preferred as the target vessel. In this article, the saphenous vein graft (SVG) patency is compared between these two main targets in the long term.Materials and Methods Postoperative control coronary angiograms were obtained and assessed from 452 patients undergoing conventional on-pump coronary artery bypass grafting with either a DRCA (n = 305) or a RPDA graft (n = 147) after an average postoperative period of 5.8 ± 4.3 years (range: 2 months–20 years; a total of 2,627 patient-years).Results The overall graft patency was 60%. The 15-year patency rate was better for the DRCA grafts than that for the RPDA grafts (32 ± 5% vs. 19 ± 6%, respectively; p = 0.001), irrespective of target vessel caliber. Other factors adversely influencing the long-term graft patency were poor target vessel quality (p = 0.002) and hypercholesterolemia (p = 0.01). On the other hand, target vessel diameter, diabetes mellitus, hypertension, chronic renal insufficiency, obesity, peripheral arterial disease, or SVG quality were not associated with poor long-term graft patency in these patients having distal-type RCA disease.Conclusions In the presence of distal and/or sequential right coronary disease, DRCA may be the target vessel of choice for bypass grafting, rather than the RPDA, mainly for better long-term SVG patency rates in this location.
Keywords: coronary artery bypass grafts surgery; CABG; atherosclerosis; restenosis